The differences in Papuan elite athletes in the anxiety perspective - Ewendi M Mangolo; Tri Setyo Guntoro; Kurdi; Miftah Fariz Prima Putra (Journal Sport Area, 2021)
Anxiety is believed to be an important psychological dimension in determining the outcome of sport matches. However, studies examining this aspect of Papuan elite athletes have never been conducted. Therefor, this study aims to reveal the differences in the anxiety amidst the Papuan elite athletes in terms of sport and gender. Furthermore, the comparative research method used involves six sports with different characteristics, namely game, martial arts, and accuracy. Subsequently, a total of 100 athletes in the PON XX preparation training camp are involved, with about 39 in the game (M= 19, F= 20), 32 in martial arts (M= 18, F= 14), and 31 in the accuracy sport (L = 14 P = 17). Furthermore, the Sport Anxiety Scale-2 (SAS-2) is used as an instrument for data collection on athlete's anxiety. Research data collection is carried out during the COVID-19 pandemic, so that the distribution of research instruments is carried out online using the google form. The research data are analyzed using descriptive and ANOVA techniques using the IBM SPSS program version 26. The results show that (1) there is no difference in anxiety between athletes in the sport of games, martial arts, and accuracy, (2) there is no difference in anxiety between male and female athletes. Although there is no difference, the anxiety that existed in athletes, especially at low and high levels, they need attention from the coach.